PSYCHOLOGICAL FACTORS AS A CORRELATE OF SPOUSAL ABUSE AMONG WORKING-CLASS WOMEN IN LAGOS METROPOLIS - Rahmat Tinuke Kamaldeen; Tiwalade Olubukola Soriyan (Universitas Pendidikan Indonesia, 2024)
Spousal abuse in marriages represents a significant problem that leads to considerable psychological distress for working-class women in Nigeria. This research examines the connections between psychological factors and spousal abuse in working-class women residing in the Lagos metropolis. The research employed quantitative analysis to evaluate the effects of depression and low self-esteem on spousal abuse. The analysis indicates a significant positive correlation between depression and spousal abuse (r = .739; p 0.05), which indicates that higher levels of depression are closely linked to a rise in incidents of spousal abuse. The study reveals a noteworthy positive correlation between low self-esteem and spousal abuse (r = .677; p 0.05), indicating that lower self-worth plays a significant role in the occurrence of spousal abuse. The findings underscore the significant influence of psychological factors in the dynamics of spousal abuse, recommending the necessity for focused interventions aimed at addressing depression and self-esteem challenges to reduce abuse among working-class women in the Lagos metropolis.